KOMPATIBILITAS DISAIN : PENENTU KINERJA WAKTU PELAKSANAAN BANGUNAN GEDUNG - Bambang Endro Yuwono; Dwi Emi Lisa Yani; Achmad Waryanto (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2018)
The cause of most projects experiencing delays is the poor quality of the design. One indication of the low quality of design is the change in design at the construction stage. Changes in design at the time of construction cause a decrease in time performance. There have been many studies related to the quality of design, but no one has specifically linked the quality of design to the time performance of project implementation. On the other hand, indicators for measuring the quality of the design have not been the same among the researchers, so it is necessary to re-examine the indicators to measure the quality of the design so that the results reflect the quality of the design that should be. The research was carried out by combining various design quality indicators that had been used by the researchers before, which allegedly influenced the time performance of building construction. The hypothesis proposed was "Improving the Quality of Design will Improve the Performance of the Implementation of Buildings". The object of research is buildings completed in the last 10 years in Indonesia. The data obtained is then tabulated and performed correlation analysis, intercorrelation, factor analysis, determinant analysis, multiple regression analysis, model test and validation. The result is that improving the quality of design will improve performance time and as a design quality determinant is design compatibility.